Biotechnology for secure biocontainment designs in an emerging bioeconomy. (October 2021) - Arnolds, Kathleen L; Dahlin, Lukas R; Ding, Lin; Wu, Chao; Yu, Jianping; Xiong, Wei; Zuniga, Cristal; Suzuki, Yo; Zengler, Karsten; Linger, Jeffrey G; Guarnieri, Michael T
Graphical abstract: Highlights: Genetically modified organisms are integral to realizing a sustainable bioeconomy. Utility of GMOs is dependent on the development of secure biosystems designs. Secure biodesigns must target maximal containment with minimal impact on fitness. Analyzing stability at scale and ecosystem impact is essential for viable design. Systems analyses and computational integration will inform predictive design. Abstract : Genetically modified organisms (GMOs) have emerged as an integral component of a sustainable bioeconomy, with an array of applications in agriculture, bioenergy, and biomedicine. However, the rapid development of GMOs and associated synthetic biology approaches raises a number of biosecurity concerns related to environmental escape of GMOs, detection thereof, and impact upon native ecosystems. A myriad of genetic safeguards have been deployed in diverse microbial hosts, ranging from classical auxotrophies to global genome recoding. However, to realize the full potential of microbes as biocatalytic platforms in the bioeconomy, a deeper understanding of the fundamental principles governing microbial responsiveness to biocontainment constraints, and interactivity of GMOs with the environment, is required. Herein, we review recent analytical biotechnological advances and strategies to assess biocontainment and microbial bioproductivity, as well as opportunities for predictive systems biodesigns towards securing a viable bioeconomy.